Pregnancy outcomes in women with Budd–Chiari syndrome or portal vein thrombosis – a multicentre retrospective cohort study. (4th October 2021) - Wiegers, HMG; Hamulyák, EN; Damhuis, SE; van Duuren, JR; Darwish Murad, S; Scheres, LJJ; Gordijn, SJ; Leentjens, J; Duvekot, JJ; Lauw, MN; Hutten, BA; Middeldorp, S; et al.
Abstract : Objective: To evaluate current practice and outcomes of pregnancy in women previously diagnosed with Budd–Chiari syndrome and/or portal vein thrombosis, with and without concomitant portal hypertension. Design and setting: Multicentre retrospective cohort study between 2008 and 2021. Population: Women who conceived in the predefined period after the diagnosis of Budd–Chiari syndrome and/or portal vein thrombosis. Methods and main outcome measures: We collected data on diagnosis and clinical features. The primary outcomes were maternal mortality and live birth rate. Secondary outcomes included maternal, neonatal and obstetric complications. Results: Forty‐five women (12 Budd–Chiari syndrome, 33 portal vein thrombosis; 76 pregnancies) were included. Underlying prothrombotic disorders were present in 23 of the 45 women (51%). Thirty‐eight women (84%) received low‐molecular‐weight heparin during pregnancy. Of 45 first pregnancies, 11 (24%) ended in pregnancy loss and 34 (76%) resulted in live birth of which 27 were at term (79% of live births and 60% of pregnancies). No maternal deaths were observed; one woman developed pulmonary embolism during pregnancy and two women (4%) had variceal bleeding requiring intervention. Conclusions: The high number of term live births (79%) and lower than expected risk of pregnancy‐related maternal and neonatal morbidity in our cohort suggest that Budd–Chiari syndrome and/or portal vein thrombosis should not be considered as an absolute contraindication for pregnancy. Individualised, nuanced counselling and a multidisciplinary pregnancy surveillance approach are essential in this patient population. Tweetable abstract: Budd–Chiari syndrome and/or portal vein thrombosis should not be considered as an absolute contraindication for pregnancy. Tweetable abstract: Budd–Chiari syndrome and/or portal vein thrombosis should not be considered as an absolute contraindication for pregnancy. Linked article This article is commented on by YY Chung & MA Heneghan pp. 618 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17002 .